2020
DOI: 10.2217/nnm-2020-0286
|View full text |Cite
|
Sign up to set email alerts
|

No Small Matter: A Perspective on Nanotechnology-Enabled Solutions to Fight COVID-19

Abstract: There is an urgent need for safe and effective approaches to combat COVID-19. Here, we asked whether lessons learned from nanotoxicology and nanomedicine could shed light on the current pandemic. SARS-CoV-2, the causative agent, may trigger a mild, self-limiting disease with respiratory symptoms, but patients may also succumb to a life-threatening systemic disease. The host response to the virus is equally complex and studies are now beginning to unravel the immunological correlates of COVID-19. Nanotechnology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 158 publications
(195 reference statements)
0
15
0
4
Order By: Relevance
“…Likewise, nanotechnology and nanoscience may open new windows in combating various pathogens including COVID‑19, in different ways such as detecting the virus, diagnosis of viral infection and nano-vaccines, such as lipid nanoparticles, for the prevention and/or the therapy of COVID-19 infection [118] , [119] , [120] , [121] , [122] , [123] , [124] , [125] , [126] , [127] , [128] , [129] .…”
Section: Application Of Nanotechnology In Virus Therapymentioning
confidence: 99%
“…Likewise, nanotechnology and nanoscience may open new windows in combating various pathogens including COVID‑19, in different ways such as detecting the virus, diagnosis of viral infection and nano-vaccines, such as lipid nanoparticles, for the prevention and/or the therapy of COVID-19 infection [118] , [119] , [120] , [121] , [122] , [123] , [124] , [125] , [126] , [127] , [128] , [129] .…”
Section: Application Of Nanotechnology In Virus Therapymentioning
confidence: 99%
“…New therapeutics and vaccines can be given by nanotechnology to counter the current pandemic; nanomedicines, though, need to be proved secure first, as all modern treatments [ 287 ]. Also, they should be well tested before launching in the market.…”
Section: Nanomedicine Solutions (Nanotechnology)mentioning
confidence: 99%
“…Another study has shown promising use of flavonoids against SARS-CoV-2 using molecular docking approaches [61] . The concern of synthetic nanomaterials use could be eliminated by employing nanoparticles arising from phyto actives [ 62 , 63 ]. Moreover, these compounds themselve can potentiate the anti-COVID-19 activity.…”
Section: Ivermectin and Covid-19mentioning
confidence: 99%